“Watch Out for Their Home!”: Disrupting Extractive Forest Pedagogies in Early Childhood Education - van Groll, Nancy; Fraser, Heather (Journal of Childhood Studies, 2022)
The frictions of living and learning in times of climate precarity, global unrest, and uncertainty require educators to consider the ways we can collectively engage in speculative pedagogies that respond to the complex, coinherited common world(s) we inhabit. This conceptual and practice-based paper considers the way early childhood education is implicated in ongoing settler colonialism. It aims to notice, generate, and stay with the trouble of stories that disrupt and unsettle the extractive and colonial dialogues about the forest as a resource and pedagogical tool.